Riparian vegetation diversity of the Banjaran River, Banyumas Regency, Central Java - Fikriyya, Nabela; Putri, Adinda Kurnia; Silalahi, Marina (Buletin Kebun Raya, 2023)
The land use of the Banjaran River continues to change in line with community social changes, which impact land conversion in riparian areas. The study aimed to determine the diversity of riparian vegetation species in the upstream and middle Banjaran Rivers and the relationship of vegetation diversity with environmental factors. The research was conducted in the riparian zone in the upstream part of the Banjaran River (Karangnangka and Kutaliman Villages) and the middle part of the Banjaran River (Kober and Kedungwuluh Villages). Environmental parameters were analyzed using the Kruskal Wallis and the independent test post-hoc test, and the relation between vegetation and environmental factors was analyzed using Canonical Correspondence Analysis. The riparian vegetation of Banjaran River found 61 species Banjaran River riparian vegetation found 61 species (25 species of trees and 40 species of understorey), 57 genera, and 33 families. The vegetation diversity can be seen in diversity index of the tree (1,47-2,36) and understorey (0,52-2,69); richness index of the tree (1,67-3,73) and understorey plants (2,31-4,17); evenness index of the tree (0,75-0,92) and understorey plants (0,22-0,87). Environmental parameter values that show significant differences are dissolved oxygen (DO) and water temperature. Cocos nucifera L. found a lot in low water temperature and soil temperature, contrary to Artocarpus heterophyllus Lam. and Nephelium lappaceum L. found a lot in high water temperature and soil temperature.